Nonfatal Firearm Injury and Firearm Mortality in High-risk Youths and Young Adults 25 Years After Detention, Chicago, Illinois, 1995-2020 - Teplin, Linda A. ([Verlag nicht ermittelbar], 2024)
This study contains data from the Northwestern Juvenile Project (NJP) Series, a prospective longitudinal study of the mental health needs and outcomes of youth in detention. The purpose of this study was to examine nonfatal firearm injury and firearm mortality in 1,829 youths in Chicago, Illinois who were involved with the juvenile justice system and to compare incidence rates of firearm mortality with the general population. The study publication is available for download.